Penerapan Aplikasi MYOB Accounting dalam Penyusunan Laporan Keuangan pada CV ABC - Zahara, Zahara; Andriani, Wiwik; Rissi, Dita Maretha; Rosalina, Eka (Universitas Batanghari Jambi, 2024)
This research aims to see and provide an overview of the preparation of financial reports using MYOB software that can be used by MSMEs in general. This research uses a qualitative approach with data collection methods using interviews, observation and documentation. Through interviews conducted with CV ABC, it shows that they still have difficulties in preparing technology-based financial reports so they use MYOB as one of the solutions to these problems. Based on observations, the use of MYOB at CV ABC has been running quite effectively so that it can have a big impact on better business development. If the preparation of financial reports has been carried out accurately, the business owner will find it easier to control his business activities. It is hoped that the use of MYOB in preparing financial reports can be maximized for various types of business lines. The better the use of MYOB, the better the quality of the preparation of financial statements. Although there are many other accounting software, the use of MYOB can be said to be more flexible in its use.